Characteristics, disease burden and costs of COPD patients in the two years following initiation of long-acting bronchodilators in UK primary care. Issue 1 (December 2015) - Punekar, Yogesh; Landis, Sarah; Wurst, Keele; Le, Hoa
Abstract Background To assess the symptomatic and cost burden among patients initiating long-acting bronchodilator (LABD) therapy and impact of adherence on healthcare resource use and costs. Methods This retrospective cohort study identified patients with COPD who were newly prescribed a LABD (long-acting muscarinic antagonist [LAMA], long-acting beta2 -agonist [LABA], a combination of LABA+LAMA or combination of LABA with inhaled corticosteroid [ICS]/LABA) between January 1, 2009 and November 30, 2013 from the UK Clinical Practice Research Datalink. Health care resource use, costs and symptom burden up to 24 months after treatment initiation were estimated. Adherence in the follow-up period was assessed using the medication possession ratio (MPR ≥80 %). Results The cohort comprised 8283 LABD initiators (16 % LABA, 81 % LAMA and 3 % LABA+LAMA) and 9246 LABA+ICS initiators with generally similar baseline characteristics; prior exacerbation rate was higher in the LABA+ICS cohort. Less than half the patients (LAMA:42 %; LABA:34 % and LABA+ICS:34 %) were adherent to their index medication. Among adherent patients, the total annual per patient cost of COPD was £3008 for LAMA initiators, £2783 for LABA initiators and £3376 for LABA+ICS initiators; primarily due to general practitioner interactions. Among patients with a Medical Research Council dyspnea score recorded during 24 months follow-up, a substantial proportion of adherent patients (LAMA: 41 %; LABA: 45 %; LABA+ICS 44 %) had clinically significant dyspnoea (MRC ≥ 3). Conclusion Cost and symptomatic burden of COPD was high among patients initiating maintenance treatment, including patients adherent with their initial treatment. General practitioner interactions were the primary driver of costs. Further, real world studies are required to address unmet needs and optimize treatment pathways to improve COPD symptom burden and outcomes.